2021
DOI: 10.3390/polym13091392
|View full text |Cite
|
Sign up to set email alerts
|

Development of Polylactic Acid Thermoplastic Starch Formulations Using Maleinized Hemp Oil as Biobased Plasticizer

Abstract: In this study, hemp seed oil was reacted with maleic anhydride in an ene reaction to obtain maleinized hemp seed oil (MHO). The use of MHO as a plasticizer and compatibilizer has been studied for polylactic acid (PLA) and thermoplastic starch (TPS) blends (80/20, respectively). By mechanical, thermal and morphological characterizations, the addition of MHO provides a dual effect, acting as plasticizer and compatibilizer between these two partially miscible biopolymers. The addition of MHO up to 7.5 phr (parts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 65 publications
1
26
0
1
Order By: Relevance
“…It was observed that by increasing the TPS content in the mixtures, the T 10 as T onset decreases (see Table 2 ), evidencing the hydrophilic character of the starch, and lower thermal stability compared to the samples with higher PLA content. This deterioration in thermal properties is due to the greater presence of amorphous phase of TPS after processing [ 33 ]. On the other hand, in the TPS-PLA mixtures, it is evident that the addition of Tween 20 generates an increase of 2 °C–3 °C in the starch degradation temperature (T d1 ), while the PLA degradation temperature (T d2 ) decreases around 4 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that by increasing the TPS content in the mixtures, the T 10 as T onset decreases (see Table 2 ), evidencing the hydrophilic character of the starch, and lower thermal stability compared to the samples with higher PLA content. This deterioration in thermal properties is due to the greater presence of amorphous phase of TPS after processing [ 33 ]. On the other hand, in the TPS-PLA mixtures, it is evident that the addition of Tween 20 generates an increase of 2 °C–3 °C in the starch degradation temperature (T d1 ), while the PLA degradation temperature (T d2 ) decreases around 4 °C.…”
Section: Resultsmentioning
confidence: 99%
“…and string matching [ 32 ]. In the same way, when analyzing the influence of maleinized hemp oil as a green plasticizer and/or compatibilizer in PLA/TPS blends, an increase in elongation at break and toughness values was achieved [ 33 ]. From these results it can be concluded that the maleinized oils mobilize the chains of the macromolecules and increase the free volume, as well as the degree of crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…Lactic polyacid has also been used in combination with starch, using hemp oil modified with maleic anhydride as plasticizer and compatibilizer. The added plasticizer showed improvements in the blend ductility and impact resistance [ 19 ]. Chitosan has also been used as a dispersed phase in TPS, incorporating it by thermomechanical methods and without the addition of compatibilizer.…”
Section: Introductionmentioning
confidence: 99%
“…The processes of the maleinization and epoxidation of vegetable oils provide greater reactivity to the oil and greater thermal stability with respect to unmodified oils. Therefore, the compatibility of the oils with PLA is improved and the plasticizing effect is increased [ 56 , 61 ]. These oils were modified from corn oil due to certain characteristics that make it interesting compared to other oils from cereals or seeds.…”
Section: Introductionmentioning
confidence: 99%